Pengaruh Variasi Massa Lilin Lebah terhadap Ketebalan Kain Blacu sebagai Alternatif Kemasan Ramah Lingkungan - Zahrani Qathrunnada; Heribertus Rudi Kusumantoro; Yoga Putra Pratama (Pusat riset dan Inovasi Nasional, 2025)
Public awareness is needed to reduce the use of single-use plastics. One effort to reduce plastic waste is by replacing chemical-based materials with natural alternatives. This study aims to analyze the effect of beeswax thickness on the type of fabric used. A quantitative method was applied by measuring the thickness of each material sample with beeswax mass variations of 10 grams, 15 grams, and 20 grams. The results showed that blacu fabric with 15 grams of beeswax had a “very good” coating thickness. Blacu fabric with 10 grams of beeswax had a “good” thickness, while 20 grams resulted in a “fair” thickness. The thickness of the fabric material varied according to the beeswax mass and affected the coating uniformity of beeswax applied to the fabric surface.